Management of Local Skin Reactions Caused by 5-FU 4% Cream for the Treatment of Actinic Keratosis: A Delphi Consensus - Gabriella Brancaccio; Giulia Briatico; Zoe Apalla; Reinhard Dummer; Jan Eklind; Nicole Basset Seguin; Brigitte Dreno; Maria Concetta Fargnoli; Pascale Guitera; Markus V. Heppt; Christoph Hoeller; Thomas Jouary; et al. (Dermatology Practical & Conceptual)
Introduction: Treatments such as 4% 5-fluorouracil (5-FU) cream have demonstrated strong efficacy in lesion clearance of actinic keratosis; however, local skin reactions (LSR) during treatment remain a significant challenge, potentially affecting patient adherence.